Association of HLA diversity with the risk of 25 cancers in the UK BiobankResearch in context - Qiao-Ling Wang; Tong-Min Wang; Chang-Mi Deng; Wen-Li Zhang; Yong-Qiao He; Wen-Qiong Xue; Ying Liao; Da-Wei Yang; Mei-Qi Zheng; Wei-Hua Jia (EBioMedicine, 2023)
Summary: Background: The human leukocyte antigen (HLA) is a highly polymorphic region, and HLA diversity may play a role in presenting tumour-associated peptides and inducing immune responses. However, the effect of HLA diversity on cancers has not been fully assessed. We aimed to explore the role of HLA diversity on cancer development. Methods: A pan-cancer analysis was performed to evaluate the effect of HLA diversity, measured by HLA heterozygosity and HLA evolutionary divergence (HED), on the susceptibility of 25 cancers in the UK Biobank. Findings: We observed that the diversity of HLA class II locus was associated with a lower risk of lung cancer (ORhetero = 0.94, 95% CI = 0.90–0.97, P = 1.29 × 10−4) and head and neck cancer (ORhetero = 0.91, 95% CI = 0.86–0.96, P = 1.56 × 10−3). Besides, a lower risk of non-Hodgkin lymphoma was associated with an increased diversity of HLA class I (ORhetero = 0.92, 95% CI = 0.87–0.98, P = 8.38 × 10−3) and class II locus (ORhetero = 0.89, 95% CI = 0.86–0.92, P = 1.65 × 10−10). A lower risk of Hodgkin lymphoma was associated with the HLA class I diversity (ORhetero = 0.85, 95% CI = 0.75–0.96, P = 0.011). The protective effect of HLA diversity was mainly observed in pathological subtypes with higher tumour mutation burden, such as lung squamous cell carcinoma (P = 9.39 × 10−3) and diffuse large B cell lymphoma (Pclass I = 4.12 × 10−4; Pclass Ⅱ = 4.71 × 10−5), as well as the smoking subgroups of lung cancer (P = 7.45 × 10−5) and head and neck cancer (P = 4.55 × 10−3). Interpretation: We provided a systematic insight into the effect of HLA diversity on cancers, which might help to understand the etiological role of HLA on cancer development. Funding: This study was supported by grants from the National Natural Science Foundation of China (82273705, 82003520); the Basic and Applied Basic Research Foundation of Guangdong Province, China (2021B1515420007); the Science and Technology Planning Project of Guangzhou, China (201804020094); Sino-Sweden Joint Research Programme (81861138006); the National Natural Science Foundation of China (81973131, 81903395, 81803319, 81802708).